Business cycles and fiscal policy: Norway 1973-93 - Einar Bowitz; Stein Inge Hove (Statistics Norway, Research Department, 1996)
Effects of fiscal policy on macroeconomic variables during 1973-93 are analysed using a disaggregated macroeconometric model of the Norwegian economy. Fiscal policy is measured as deviations from estimated trends for disaggregated policy variables. The policy effects are related to the cyclical situation of the economy. Variations in fiscal policy instruments have reduced output volatility during 1973-93 by approximately 10 per cent, according to our results. On average the behaviour of local government has been procyclical. Partial effects of various fiscal instruments are calculated. During certain episodes fiscal policy appeared procyclical, an effect that is due to the aim of stabilizing the current account.
Keywords: C53; E32; E37; E63; E65; 330; Business cycles; Fiscal policy; Macroeconometric modelling.